DEVELOPMENT OF CONTEXTUAL MEDIA DIORAMA OF WATER CYCLE IN SCIENCE SUBJECT IN ELEMENTARY SCHOOL - Tasya Humaira; Mimin Ninawati (Jurnal Cakrawala Pendas, 2023)
This research is motivated by the fact that there are still many students who do not understand the water cycle material in science lessons because teachers do not use learning media in the learning process, this causes a lack of student understanding of the water cycle material in science lessons. The purpose of this study is to develop water cycle diorama media so that it meets the eligibility criteria to be implemented in science lesson content. This research uses the Research and Development (R&D) method or commonly referred to as development, with a 4D model. In the 4D model, there are several stages such as, define, design, develop, and disseminate. The data collection process uses descriptive data results through questionnaires. The descriptive data was obtained from responses and suggestions by experts and respondents of grade V students. The subject of this study was grade V students of SDN Ciracas 11 Pagi. The study was conducted in small groups and large groups. A small group consists of 5 students of Class V, while for large group consists of 32 students of Class V. Based on the results of validation by media experts and material experts, it shows that water cycle diorama media is very suitable to be used as a learning medium on water cycle material and the results of research to small groups with 5 students and large groups with 32 students,   It was concluded that this water cycle diorama media is also very suitable to be used as a learning medium for water cycle material in science lesson content in grade V elementary school. The results of validation by media experts got a very valid category, for the results of validation by material experts got a very valid category, and the responses obtained by 5 students in this study got a very decent category, and responses to 32 students got a very decent category. Based on the results of the acquisition, it was concluded that the water cycle diorama media in the content of science lessons for grade V elementary school was said to be very feasible to use. Penelitian ini dilatarbelakangi oleh masih banyak siswa yang belum memahami materi siklus air pada pelajaran IPA, dikarenakan guru tidak menggunakan media pembelajaran dalam proses pembelajaran, hal ini menyebabkan kurangnya pemahaman siswa terhadap materi siklus air muatan pelajaran IPA. Tujuan penelitian ini adalah untuk mengembangkan media diorama siklus air sehingga memenuhi kriteria kelayakan untuk dapat diimplementasikan pada muatan pelajaran IPA. Penelitian ini menggunakan metode Research and Development (R&D) atau biasa disebut dengan pengembangan, dengan model 4D. Pada model 4D terdapat beberapa tahapan seperti, define (pendefinisian), design (perancangan), develop (pengembangan), disseminate (penyebarluasan). Proses pengumpulan data menggunakan hasil data deskriptif melalui angket. Data deskriptif tersebut didapatkan dari tanggapan dan saran oleh para ahli dan responden siswa kelas V. Subjek penelitian ini adalah siswa kelas V SDN Ciracas 11 Pagi. Penelitian ini dilakukan dalam kelompok kecil dan kelompok besar. kelompok kecil terdiri dari 5 siswa Kelas V, sedangkan untuk kelompok besar terdiri dari 32 siswa kelas V. Berdasarkan hasil validasi oleh ahli media dan ahli materi menunjukan bahwa media diorama siklus air sangat layak digunakan sebagai media pembelajaran pada materi siklus air pada muatan pelajaran IPA di kelas V SD. Hasil validasi oleh ahli media mendapat kategori sangat valid, untuk hasil validasi oleh ahli materi mendapat kategori sangat valid, dan respon yang didapatkan pada 5 siswa dalam penelitian ini mendapat kategori sangat layak, serta  respon kepada 32 siswa memperoleh kategori sangat layak. Berdasarkan hasil perolehan disimpulkan bahwa media diorama siklus air pada muatan pelajaran IPA untuk kelas V SD dikatakan sangat layak digunakan.